Transversus Abdominis Plane Block in Colorectal Surgery: A Meta-Analysis - Viderman, Dmitriy; Aubakirova, Mina; Abdildin, Yerkin G. (Frontiers in Medicine, 2022)
Acute postoperative pain is one of the most common concerns during the early postoperative period in colorectal surgery. Opioids still represent the cornerstone of postoperative pain management, yet they often result in significant side effects such as nausea and/or vomiting, sedation, urinary retention, delayed recovery of colonic motility, respiratory depression, and postoperative ileus. Transversus abdominis plane (TAP) block has been widely used for postoperative analgesia in various abdominal surgeries. The primary aim of this meta-analysis was to compare the postoperative opioid requirements of patients in the TAP block group and the control group (placebo). The secondary aims included evaluation of the efficacy of TAP blocks in postoperative pain management, the measurement of time to first request for opioids, the measurement of length of hospital stay (LoS), and the documentation of postoperative nausea and/or vomiting. We searched for articles reporting the results of randomized controlled trials (RCTs) on the application of TAP block in colorectal surgery published before September 2021. Eight RCTs involving 615 patients were included in the meta-analysis. Seven articles reported the results of TAP blocks in laparoscopic surgery and eight in both laparoscopic and open surgery. The need for opioids and the intensity of pain at rest within 24 h after laparoscopic and combined (laparoscopic and open) surgeries were significantly lower in the TAP block group compared with the “no block” group. The intensity of pain during coughing within 24 hours after laparoscopic surgery was significantly lower in the TAP block groups compared to the groups without block. There were no statistically significant differences between the TAP block and “no block” groups in overall (over the entire hospital stay) postoperative opioid consumption and length of hospital stay after laparoscopic surgery, as well as in postoperative nausea and vomiting after laparoscopic and combined surgeries.